Effects of organic fertilization on production and postharvest quality of coriander (Coriandrum sativum L.) (Research, Society and Development, 2020)
This work compares the productivity and postharvest quality of C. sativum produced in organic and conventional systems. We used a randomized block experiment with five treatments and six repetitions each. Treatments comprised a negative control (C-: without fertilization), three doses of bovine manure as organic fertilization (35, 70, and 105 kg of N ha -1, named T35, T70, and T105 respectively), and a positive control (C+: 70 Kg of N ha -1 of conventional fertilization). We evaluated the morphometry, productivity, and physical-chemical characteristics of all plants used. The effect of organic fertilizer doses was analyzed using polynomial regressions. The differences among negative control, the positive control, and the organic fertilization with 70 Kg of N ha -1 of manure were tested with orthogonal contrasts. The doses of N used in organic fertilization influence the water and protein activity of C. Sativum leaves, promoting their decrease. The contrasts influenced the productivity, total fresh weight, fresh weight of the aerial part, dry weight of the aerial part, dry weight of the root, the total dry weight, water activity, titratable acidity, soluble solids, carotenoids, total chlorophyll, chlorophyll b, C. sativum was influenced by comparisons. The conventional production system using ammonium sulfate as the source of nitrogen promoted higher productivity and better postharvest quality in the culture of C. sativum. The period of implementation of bovine manure hampered the organic system. We suggest the fertilization with bovine manure before sowing, providing the necessary time for its mineralization during the cultivation cycle.